The Quality of Visual Interior Elements on Psychological Comfort of Postpartum Women in the VVIP Room of RSIA Melati Husada Malang - Almira Firdania Isna Johanda; Herry Santosa (Jurnal Mahasiswa Departemen Arsitektur, 2023)
The interior of the postnatal hospital room has a significant influence on psychological comfort in postpartum women. A comfortable and positive interior atmosphere can reduce the stress and anxiety experienced by postpartum women. Interior visual elements such as colour, lighting, decoration, and interior vegetation can provide psychological comfort to patients. RSIA Melati Husada is the only RSIA in Malang with the highest title of Plenary and the majority of its patients feel comfortable with its interior conditions. However, there are differences in interior design between previous studies and the interior in this RSIA. The purpose of this study is to identify how the interior design of the hospital room can be a reference and to find out the visual elements of the interior of the hospital room that are able to influence the psychological comfort of postpartum women. The research method is descriptive qualitative with a Post-Positivism paradigm to compare previous theories with field conditions. The results of the comparison analysis between the Grand Theory and empirical data were validated by interviews with postpartum patients to determine their suitability. The results of the data triangulation discussion resulted in an interior design reference that was able to influence the psychological comfort of postpartum patients. In addition, it was found that the visual interior elements that are able to influence psychological comfort in postpartum women are elements of colour, material, decoration, lighting, view, and privacy, and based on patient preferences, the element that most influences their psychological comfort is the decoration element. Keywords: interior visual elements, hospital room, psychological comfort, postpartum patient.